2008
DOI: 10.1248/bpb.31.1017
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Activity of (-)-Carvone: Evidence of Association with Decreased Peripheral Nerve Excitability

Abstract: (؊)-Carvone is a monoterpene ketone that is the main active component of Mentha plant species like Mentha spicata. This study aimed to investigate the antinociceptive activity of (؊)-carvone using different experimental models of pain and to investigate whether such effects might be involved in the nervous excitability elicited by others monoterpenes. In the acetic acid-induced writhing test, we observed that (؊)-carvone-treated mice exhibited a significant decrease in the number of writhes when 100 and 200 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 30 publications
6
64
0
Order By: Relevance
“…Previous studies suggested that the CNS depression and the nonspecific muscle relaxation effect can reduce the response of motor coordination and consequently might invalidate the nociceptive behavioral tests results (Gonçalves et al, 2008). We did not see any interference with the motor coordination of the animals in the rota-rod test, therefore eliminating a nonspecific muscle relaxation effect of EO at the doses used.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Previous studies suggested that the CNS depression and the nonspecific muscle relaxation effect can reduce the response of motor coordination and consequently might invalidate the nociceptive behavioral tests results (Gonçalves et al, 2008). We did not see any interference with the motor coordination of the animals in the rota-rod test, therefore eliminating a nonspecific muscle relaxation effect of EO at the doses used.…”
Section: Discussionmentioning
confidence: 42%
“…Mice able to remain on the Rota-rod apparatus (AVS ® , Brazil) longer than 180 s (9 rpm) were selected 24 h before the test according to Gonçalves et al (2008). Then the selected animals were divided into five groups (n=8) and treated i.p.…”
Section: Rota-rod Testmentioning
confidence: 99%
“…Nevertheless, there were described anxiolytic and antidepressant effects of A. polystachya (Mora et al, 2005;Hellion-Ibarrola et al, 2008). Also, it has been described the presence of (-)-carvone in the essential oil of A. polystachya (Werdin-González et al, 2010), which was related to antispasmodic effect of Mentha genus (de Goncalves et al, 2008) as well as other terpenic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…and commonly extracted from its leaves (2). R-(-)-carvone (abbreviated as (-)-Cv) is an enantiomer of carvone being the major constituent of peppermint (Mentha spicata) EO and displaying antinociceptive and anticonvulsant activities in addition to other pharmacological effects (3,4). However, few studies have been proposed to elucidate the mechanisms involved with these pharmacological profiles of (-)-Cv at the cellular level.…”
Section: Introductionmentioning
confidence: 99%